ANALYSIS OF "HARD CHROME" PERFORMANCE IMPROVEMENT IN MAINTENANCE ENGINE SERVICES INDUSTRY - Prabowo, Rommy Febri; Hasbullah, Hasbullah (Journal of Industrial Engineering & Management Research, 2020)
- In this study, the company under study is an Industrial Maintenance and Repair Engine with Hard Chrome as the main service. In its activities, the problem is the increase in customer complaints regarding the results of repair work and the results of the process, so that the spare parts that have been repaired must return to the workshop for rework. In the step of making improvements, the DMAIC approach is carried out and evaluates it by calculating the Overall Equipment Effectiveness (OEE) and comparing it with OEE before improving. and then the analysis discusses the factors that affect the effectiveness of the Hard Chrome machine, which are found in the six major losses and other problems where the fishbone diagram analysis method is used. Based on the results of calculations using the analysis of six big losses, two dominant factors were found, namely deffect losses and reduced speed losses, where the cumulative percentage value of deffect losses was 70.14% and reduced speed losses was 27.91%. After that, a discussion was carried out using 5W1H as Improve with the results of the average OEE value for Hard Chrome machines for the period March to June 2020 of 70.26%, where the average value of Availability = 89.65%, Performance = 82, 02% and Quality = 98.38%.